2017
DOI: 10.1007/s11739-017-1612-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac biomarkers of acute coronary syndrome: from history to high-sensitivity cardiac troponin

Abstract: The role of cardiac troponins as diagnostic biomarkers of myocardial injury in the context of acute coronary syndrome (ACS) is well established. Since the initial 1st-generation assays, 5th-generation high-sensitivity cardiac troponin (hs-cTn) assays have been developed, and are now widely used. However, its clinical adoption preceded guidelines and even best practice evidence. This review summarizes the history of cardiac biomarkers with particular emphasis on hs-cTn. We aim to provide insights into using hs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(184 citation statements)
references
References 52 publications
2
143
0
7
Order By: Relevance
“…Lapatinib hardly altered the echocardiogram variables and NT-proBNP, suggesting that lapatinib may not damage the LV systolic and diastolic function during the acute phase. cTnI has known to act on myocardial contraction by regulating the calcium-dependent interaction of actin and myosin 16,17 . Although the mechanisms by which cTnI is released into the bloodstream are not fully understood, it is a more sensitive blood biochemical markers for cardiac injuries than CK, AST, and LDH 16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lapatinib hardly altered the echocardiogram variables and NT-proBNP, suggesting that lapatinib may not damage the LV systolic and diastolic function during the acute phase. cTnI has known to act on myocardial contraction by regulating the calcium-dependent interaction of actin and myosin 16,17 . Although the mechanisms by which cTnI is released into the bloodstream are not fully understood, it is a more sensitive blood biochemical markers for cardiac injuries than CK, AST, and LDH 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…cTnI has known to act on myocardial contraction by regulating the calcium-dependent interaction of actin and myosin 16,17 . Although the mechanisms by which cTnI is released into the bloodstream are not fully understood, it is a more sensitive blood biochemical markers for cardiac injuries than CK, AST, and LDH 16,17 . It has been reported that the elevation of cTnI has been observed with the repeated administration of lapatinib combined with paclitaxel or trastuzumab 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin is a specific cardiac structural protein associated with myocyte injury of any type . Although elevated blood Cardiac troponin is not specific to acute coronary events, Cardiac troponin testing is highly sensitive in detecting small amounts of myocardial necrosis .…”
Section: Classification Of MImentioning
confidence: 99%
“…3 Cardiac troponin is a specific cardiac structural protein associated with myocyte injury of any type. 7,8 Although elevated blood Cardiac troponin is not specific to acute coronary events, Cardiac troponin testing is highly sensitive in detecting small amounts of myocardial necrosis. 7 In a study examining the utility of high-sensitivity Cardiac troponin assays, more high-risk patients presenting to the emergency department (ED) with unspecified chest pain were identified and admitted to the hospital than when conventional Cardiac troponin assays were used.…”
Section: Diagnosis Of Nstemimentioning
confidence: 99%
“…Cardiac troponin biomarkers are an essential component used to diagnose acute MI [18]. In the late 1980s, cTnI was proposed as marker of cardiac cell death, and is now widely used and established as the guideline-recommended marker in order to assist in the diagnosis of myocardial injury in clinical pathologies, such as post-surgery myocardium trauma, chemotherapy cardiotoxicity and many other diseases related to cardiac muscle injury [19]. This study aims to measure serum levels of IL-33, CRP and troponin in CAD patients.…”
Section: Introductionmentioning
confidence: 99%